Pengaruh budaya organisasi, pengembangan karier dan self efficacy terhadap kinerja karyawan - Jenny Fauziah; Jonathan Pongtuluran; Musdalifah Aziz (Faculty of Economics and Business Mulawarman University, 2016)
The purpose of this study to determine, simultaneously, the effect of Organizational Culture, Career Development, and Self-Efficacy on the performance of employees at PT. Pandu Siwi Sentosa Samarinda and know one of the independent variables were the dominant influence on the performance of employees at PT. Pandu Siwi Sentosa Samarinda Basic theory used human resources management by using multiple linear regression analysis tool with 32 samples. The conclusion of this study: From the multiple linear regression equation is known that all variable values have a positive sign (+) so the organizational culture variables (X1), Career development variables (X2), and self-efficacy variables (X3) jointly positive and significant effect on the performance of employees of PT . Pandu Siwi Sentosa Samarinda.This means that if there is improvement in the quality of the variable organizational culture, career development, and self-efficacy will improve the performance of employees of PT. Pandu Siwi Sentosa Samarinda, otherwise if a decline in the quality of work ethics, supervision and discipline it will degrade the performance of employees of PT. Pandu Siwi Sentosa Samarinda. For that efforts to improve the quality of organizational culture, career development, and self-efficacy need to be done by. Pandu Siwi Sentosa Samarinda. Value of the correlation coefficient (R) showed a very strong relationship between the performance of employees of PT. Pandu Siwi Sentosa Samarinda (the dependent variable) with the organizational culture, career development, and self-efficacy. The results of the calculation of the coefficient of determination indicates that the effect of independent variables consisting of variables organizational culture, career development, and self-efficacy were able to explain the dependent variable performance of employees of PT. Pandu Siwi Sentosa Samarinda and there is still explained by other variables not included in this study.Keyword: Organizational Culture, Career Development, Self Efficacy-Performance